The isotope effects in RFP magnetic configuration. (12th October 2021) - Lorenzini, R; Gobbin, M
Abstract: The comparison between deuterium and hydrogen plasmas at high current in the RFX-mod experiment proves that the reversed field pinch configuration experiences the isotope effect in a way analogous to tokamak experiments. Both energy and particle confinement exhibit a favourable scaling with the isotope mass M i, respectively, as M i 0.3 and as M i 0.45 . This effect is mainly due to the mitigation of transport at the edge, which is driven by electrostatic fluctuations, although a mitigation of the stochastic transport in the plasma core is also observed. As in tokamaks, the MHD properties are modified when the gas mass is changed. The most evident modification regards the spectrum of tearing modes that are more stable in deuterium, so that the duration and the purity of quasi single helicity (QSH) phases are enhanced. The thermal structures that develop during the QSH phases enclose a plasma volume that is wider in deuterium discharges than in hydrogen ones.